Cultural production on social media: case study of occupied town - Soklakov, Maksym (Ukrainian Cultural Studies, 2024)
Background. Since the start of the Russian full-scale invasion, major transformations in the media consumption of Ukrainians have occurred. Social media platforms are utilized as means of informational warfare and play a major role in the cultural production of everyday content on both local and nationwide levels. The logic of content production on social media platforms fosters the constitution of the so-called ’digital public sphere’, and in this way affects the Ukrainian public sphere overall. The goal of this article is to explicate the potential uses of social media platforms as sources of research, that allow to observe the cultural production on the occupied territories, and in this way foster the creation of policies for the re-integration. The research objectives are to identify established social media informational infrastructures in the occupied town of Berdiansk and explore the utilized principles of cultural production of the image of the city, through the concept of the digital public sphere. Methods. Case studies, content analysis, netnographic study, narrative, and textual cultural analysis, interdisciplinary analysis of metadata and statistic data available online, and cultural history approach – reconstruction of the logic of material devices, and functioning of virtual spaces overall. Results. Two simultaneous and mutually exclusive informational infrastructures are established, Ukrainian and Russian. Both are creating mutually exclusive but intersecting images of the city, framing ongoing events as either occupation or ’liberation’. The images of the city are constituted via the cultural production of everyday content on social media platforms. This cultural production follows the logic of attention economy. Conclusions. Russian informational military units and occupational administrations actively utilize social media platforms as an instrument of informational warfare, to reinforce and legitimize their presence. However, at the same time, social media affordances foster the emergence of new practices of resistance from the Ukrainian side. The openness of the network environment allows Ukrainian citizens under occupation to stay in touch with the Ukrainian media sphere, and vice versa. The digital public sphere allows us to research the transformations occurring under occupation. New forms of social and cultural production emerge within a network environment of social media platforms, particularly within a situation of a full-scale war.